Structural changes observed during the reversible hydrogenation of Mg(BH4)2 with Ni-based additives - Saldan, I.; Hino, S.; Humphries, Terry; Zavorotynska, O.; Chong, M.; Jensen, C.; Deledda, S.; Hauback, B. (American Chemical Society, 2014)
The decomposition and rehydrogenation of ?-Mg(BH4)2 ball milled together with 2 mol % of Ni-based additives, Ninano, NiCl2, NiF2, and Ni3B, has been investigated during one hydrogen desorption-absorption cycle. Under the applied ball-milling conditions, no mechanochemical reactions between ?-Mg(BH4)2 and Niadd were observed. Hydrogen desorption carried out at temperatures of 220-264 °C resulted for all samples in partial decomposition of Mg(BH4)2 and formation of amorphous phases, as seen by powder X-ray diffraction (PXD). PXD analysis after rehydrogenation at temperatures of 210-262°C and at pressures between 100 and 155 bar revealed increased fractions of crystalline ß-Mg(BH4)2, indicating a partial reversibility of the composite powders. The highest amount of [BH4]- is formed in the composite containing Ni3B. Analysis by X-ray absorption spectroscopy performed after ball milling, after desorption, and after absorption shows that the Ni3B additive remains unaffected, whereas NiCl2 and NiF2 additives react with Mg(BH4)2 during the hydrogen desorption-absorption and form compounds with a local structure very similar to that of amorphous Ni3B. Multinuclear NMR spectroscopy confirms the partial reversibility of the system as well as the formation of [B10H10]2- during hydrogen absorption. The presence of [BnHn]2- (n = 10, 12) was also detected by infrared (IR) spectroscopy of the dehydrogenated and rehydrogenated samples. The IR measurements give no clear indication that ions containing B-H-B bridged hydrogen groups were formed during the H-sorption cycle.